How can applicants' reactions to scholastic aptitude tests be improved? A closer look at specific and general tests - Denker, Marek; Schütte, Clara; Kersting, Martin; Weppert, Daniel; Stegt, Stephan Josef (Frontiers in Education, 2023)
Since the 1980s, scientific interest in applicant reactions to admission procedures has been growing. Several theoretical frameworks and evaluation questionnaires were developed. Most researchers asked potential participants about their attitudes—what is missing, however, are studies of applicants who have actually taken part in selection procedures. In addition, applicant reactions to student selection procedures receive less attention than applicant reactions to personnel selection procedures. Furthermore, tests and testing conditions continue to develop, e.g., by online based testing and test supervision at home (“proctoring”). Therefore, we used a standardized questionnaire measuring the overall test evaluation as well as different dimensions of acceptance, namely face validity, controllability and absence of strain to have a closer look at six scholastic aptitude tests. We added items in order to get deeper insights into situational aspects. Results of 2052 test participants show that applicants have a preference for specific tests and for shorter tests. Situational aspects as privacy, working conditions and prior information have an influence on perceptions of applicants. Proctored testing is evaluated positively, but taking the test at a test-center is still rated more favorably. Practical implications are discussed.